Retrieval of Recent Autobiographical Memories is Associated with Slow-Wave Sleep in Early AD - Rauchs, Géraldine (Frontiers Media S.A., 2013)
Autobiographical memory is commonly impaired in Alzheimer’s disease (AD). However, little is known about the very recent past which is though highly important in daily life adaptation. In addition, the impact of sleep disturbances, also frequently reported in AD, on the consolidation, and retrieval of autobiographical memories remains to be assessed. Using an adaptation of the TEMPau task, we investigated the neural substrates of autobiographical memory for recent events and the potential relationship with sleep in 14 patients with mild AD. On day 1, autobiographical memory was explored across three periods: remote (18–30 years), the last 2 years and the last month. After testing, sleep was recorded using polysomnography. The next day, AD patients benefited a resting-state (18)FDG-PET scan and a second exploration of autobiographical memory, focusing on the very recent past (today and yesterday). Total recall and episodic recall scores were obtained. In addition, for all events recalled, Remember responses justified by specific factual, spatial, and temporal details were measured using the Remember/Know paradigm. Retrieval of autobiographical memories was impaired in AD, but recall of young adulthood and very recent events was relatively better compared to the two intermediate periods. Recall of recent events (experienced the day and the day preceding the assessment) was correlated with brain glucose consumption in the precuneus and retrosplenial cortex, the calcarine region, the angular gyrus, and lateral temporal areas. AD patients also provided more Justified Remember responses for events experienced the previous-day than for those experienced the day of the assessment. Moreover, Justified Remember responses obtained for events experienced before sleep were positively correlated with the amount of slow-wave sleep. These data provide the first evidence of an association between the ability to retrieve recent autobiographical memories and sleep in mild AD patients.